Tax Rate and its Determinants: An Opinion from Ibn Khaldun - Abdul Ghafar Ismail (Ibn Haldun University, 2017)
Tax is an alternative method for a country to obtain revenue for spending. But the issue arises when there are differences of opinion on the tax rate. Economists argue that to obtain higher tax revenue, it is necessary to lower the tax rate. In this paper, an analysis of tax rates is conducted by looking at the findings of Ibn Khaldun in his book Muqaddimah. This study also examines other hypotheses related to taxation. The findings show that the optimal rate of taxation can be determined.